The compounding effect of tariffs on medicines: Estimating the real cost of emerging markets' protectionism - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2017)
Even low import tariff rates have a significant compounding effect on the final retail price of medicines, which in turn impacts on affordability. While much of the "access to affordable medicines" debate is about intellectual property rights (IPRs) and business practices of pharmaceutical manufacturers, import duties and national protectionism are swept under the political rug. In this paper, we provide a synopsis of tariff barriers for exports of pharmaceutical products to the world's major low and middle income countries (BRICS-MINT countries). Studying the impact on final prices for consumers, we estimate that the annual compounded financial burden of import tariffs on pharmaceuticals and prevailing trade facilitation inefficiencies is highest for China (up to 6.2bn USD), Russia (up to 2.8bn USD), Brazil (up to 2.6bn USD) and India (737mn USD), followed by Mexico (663mn USD), Turkey (290mn USD), Indonesia (251mn USD), South Africa (177mn USD) and Nigeria (60,000 USD). For Brazil and India, tariffs on medicines increase their final price by up to 80 per cent of the original sales price ex factory. As most BRICS-MINT governments directly buy or settle patients' invoices for a bulk of medicine products, the sum of all tariff-induced premiums on final prices for pharmaceuticals tends to exceed by far the tariff revenues initially collected by these governments' customs authorities. While import tariffs on medicines can cause substantial net losses for governments, taxpayers and patients, they effectively work as a subsidy for companies along national distribution chains. This may lead to a political economy, in which customs authorities and pharmaceutical distributors may have a common interest in maintaining (high) import tariffs. We call for all low and middle income countries to join the "zero for zero" pharmaceutical agreement, which would help to significantly cut the costs of medicines in general, reduce obscurity and absurdities in government spending and create better conditions for the access to medicines for low-income patients in these countries.
Keywords: 330